Growing Leadership Spirit in Students Through the Concept of Khalifah fil Ardhi - Rohana, Rohana (al-Iltizam: Jurnal Pendidikan Agama Islam, 2023)
Abstract: This paper describes the concept of khalifah fil ardhi as God's representative in prospering the earth. Humans as khalifah fil 'ard have two meanings, namely khalifah in the sense of head of state and caliph as a substitute and inhabitant of Allah's earth. This research includes literature study, The type of data collected is in from various articles, papers,library sources and appropriate documents. The data obtained,  then collected,   compiled,   reviewed,   analyzed,  and concluded so as to obtain recommendations regarding the study of literature. This paper aims to instill awareness in students to realize the spirit of leadership as an effort to build, care for, and preserve the earth. Students as educated human beings have an urgent task as a leader and it is necessary to develop a leadership spirit. Things that students can do include; (1) become a learner (learner), (2) become an observer (heart) and, (3) become a thinker (thinker) and care. These three things are expected to be understood and applied in everyday life as an effort to foster a leadership spirit in students. Keywords: Leadhership, Student, Khalifah fil ArdhiAbstrak: Tulisan ini menjelaskan tentang konsep khalifah fil ardhi sebagai wakil Tuhan dalam memakmurkan bumi. Manusia sebagai khalifah fil ardhi mempunyai dua arti, yaitu khalifah dalam arti kepala negara dan khalifah sebagai pengganti dan penghuni bumi Allah Swt. Penelitian ini termasuk ke dalam jenis penelitian studi literature. Jenis data yang dikumpulkan berupa hasil penelitian dari berbagai artikel, makalah, sumber pustaka dan dokumen yang sesuai. Data yang diperoleh kemudian dikumpulkan, disusun, ditelaah, dianalisis, dan disimpulkan sehingga diperoleh rekomendasi terkait kajian kepustakaan. Tulisan ini bertujuan untuk menanamkan kesadaran pada mahasiswa agar terwujudnya jiwa kepemimpinan sebagai upaya membangun, merawat, dan melestarikan bumi. Mahasiswa sebagai manusia yang terpelajar mempunyai tugas yang urgent sebagai pemimpin dan perlu ditumbuhkannya jiwa kepemimpinan. Hal yang dapat dilakukan mahasiswa diantaranya; (1) menjadi seorang pem(belajar), (2) menjadi seorang pemer(hati) dan, (3) menjadi seorang pe(mikir) dan peduli. Ketiga hal tersebut diharapkan dapat dipahami dan diterapkan dalam kehidupan sehari-hari sebagai upaya dalam menumbuhkan jiwa kepemimpinan pada diri mahasiswa.Kata Kunci: Jiwa Kepemimpinan, Mahasiswa, Khalifah fil Ardhi